Research hotspots and frontiers in post-stroke dysphagia: a bibliometric analysis study - Guo, Bilian; Liu, Mengwei; Wang, Zhiyong; Yan, Zhipeng (Frontiers in Neurology, 2024)
Background Dysphagia is a common complication of stroke that can result in serious consequences. In recent years, more and more papers on post-stroke dysphagia have been published in various journals. However, there is still a lack of bibliometric analysis of post-stroke dysphagia. This study visually analyzes the global research situation of post-stroke dysphagia from 2013 to 2022, aiming to explore the current research status, frontier trends, and research hotspots in this field. Methods Articles and reviews relevant to post-stroke dysphagia were obtained and retrieved from the Web of Science core collection database in the last 10 years (from 2013 to 2022). CiteSpace and Microsoft Excel 2019 were used for bibliographic analysis. Results A total of 1,447 articles were included in the analysis. The number of publications showed an overall upward trend, from 72 in 2013 to 262 in 2022. The most influential authors, institutions, journals, and countries were Hamdy S, University of London, Dysphagia, and the People's Republic of China. An analysis of keywords and the literature indicated that current studies in the field of post-stroke dysphagia focused on dysphagia and aspiration, dysphagia classification, dysphagia rehabilitation, and daily living. Conclusion This bibliometric analysis reveals the latest advancements and emerging trends in the field of post-stroke dysphagia, spanning the years 2013 to 2022. It highlights the paramount importance of conducting large-scale randomized controlled trials examining the efficacy of dysphagia screening protocols and non-invasive intervention techniques in improving the quality of life for these patients. Such research efforts hold significant academic implications for the development of evidence-based treatment strategies in this field.